PERBANDINGAN EMISI GAS BUANG MENGGUNAKAN BAHAN BAKAR PERTALITE DENGAN BAHAN BAKAR GAS ELPIJI PADA MESIN TRIARROWS TR200 - Budiyono Budiyono; Imam Prasetyo (ROTOR, 2020)
Indonesia is one of the countries with the third highest level of air pollution in the world. The contribution of motor vehicle exhaust emissions as the largest source of air pollution reaches 60-70%, compared to industry which only ranges between 10-15%. The purpose of this research is to find out the Comparison of Flue Gas Emissions Using Pertalite Fuel with LPG Fuels on the Tr200 Triarrows Engine , The testing place at the Mechanical Engineering Lab of the University of Muhammadiyah Pekajangan Pekalongan, the research method using descriptive data analysis methods and as a dependent variable CO and HC flue gas and independent variables are 2500 rpm, 3000 rpm, 3500, 4000 rpm, 4500 rpm and 5000 rpm. Tests were conducted to determine the value of exhaust emissions on pertalite fuel and LPG gas fuel on the Triarrows Tr200 Generator. From the results of the study it was found that some significant decreases in the value of CO gas emission occurred at 3500 rpm - 5000 rpm which is the concentration decreased by 7.97% from 8.07% to 0.1% at 3500 rpm. While the concentration of HC gas emissions which is very significant at 2500 rpm - 5000 rpm which is the value of concentration decreased by 3945 ppm from 4412 ppm to 467 ppm at 3000 rpm. Keywords: Generator, Pertalite, Flue Gas Emissions, CO, HC